2020
DOI: 10.1186/s12906-020-03016-0
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD analysis of Hyssopus Cuspidatus Boriss extract and mensuration of its antioxygenation property

Abstract: Background Hyssopus cuspidatus Boriss has been used as an important ethnomedicinal plant for long to eliminate phlegm, relieve cough and as well as having antibacterial, antioxygenation, and antitumor activities. In this study, the polyphenol contents, flavonoid contents, free radical scavenging assay and animal antioxygenation property assay of ethanol extract of H. cuspidatus were measured. Methods This study determined the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
(39 reference statements)
0
11
2
Order By: Relevance
“…However, the composition of traditional Chinese medicine is complex, and it is not enough to control the quality of the whole preparation only by the two. Highperformance liquid chromatography-diode array detector (HPLC-DAD) is an effective method for chemical analysis, which has been well established in a previous study [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the composition of traditional Chinese medicine is complex, and it is not enough to control the quality of the whole preparation only by the two. Highperformance liquid chromatography-diode array detector (HPLC-DAD) is an effective method for chemical analysis, which has been well established in a previous study [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The total polysaccharide contents (TPCCs), total polyphenol contents (TPCs) and total flavonoid contents (TFCs) in the above extracts were analyzed according to current literatures ( Song et al, 2016 ; Liao et al, 2020 ; Zhao et al, 2020 ; Fanali et al, 2021 ), and described in brief as follows.…”
Section: Methodsmentioning
confidence: 99%
“…TFCs were determined with UV colorimetric assay ( Zhao et al, 2020 ). In brief, 0.5 ml of chaga extracts was added to 1 ml of sodium nitrite, and allowed to sit for 6 min, 1 ml of 10% aluminum nitrate was then added, and allowed to sit for another 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…H. cuspidatus contains a variety of chemical components, including volatile oils, flavonoids, organic acids, and lipids [ 10 , 11 ]. In recent years, H. cuspidatus and its extractions have played an important role in the treatment of asthma [ 12 , 13 ]. Pharmacological studies have demonstrated that H. cuspidatus can treat asthma through its anti-inflammatory and antibacterial effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%